Geschichte Spaniens. [Von L.M. Rogalin, S.D. Skaskin, N.I. Mizkun u.a. Ins Deutsche übertr. von B. Huth] (Rütten & Loening, 1955)
Mit Abbn, Bibliogr. und Krtn. Originaltitel: Ispanija (Istoriueskij ouek).